Product market integration and labour markets: aggregate gains at the cost of more inequality? - Torben M. Andersen; Allan Sørensen (Institute for the Study of Labor (IZA), 2007)
Important labour market consequences of globalization may arise via product market integration which affects the room for wage negotiations and generates job creation and destruction through structural changes. We find in a Ricardian trade model that aggregate increases in wages and employment may conceal important differences across sectors/groups driven by a different balance between protection and specialization rents. In particular, wage inequality tends to be U-shaped, at first decreasing and then increasing in the process of product market integration. Consequently, there are gains in both the efficiency and the equity dimension until the level of integration reaches a certain level at which a trade-off arises
urn:nbn:de:101:1-20080425402
Keywords: 330; Globalisierung; Internationale Arbeitsteilung; Außenhandelseffekt; Lohnstruktur; Beschäftigungseffekt; Arbeitsmarkt; Theorie